Integrating ecological and recreational functions to optimize ecological security pattern in Fuzhou City - Junting Bai; Rui Sun; Yifan Liu; Jie Chen; Xiaohe Li (Scientific Reports)
Abstract The scientific establishment of the Ecological Security Pattern (ESP) is crucial for fostering the synergistic development of ecological and recreational functions, thereby enhancing urban ecological protection, recreational development, and sustainable growth. This study aimed to propose a novel method of constructing ESP considering both ecological and recreational functions, and to reconstruct ESP by weighing the relationship between ecological protection and recreational development. Utilizing Fuzhou City as a case study, a comprehensive application of methodologies including Morphological Spatial Pattern Analysis (MSPA), landscape connectivity analysis, ArcGIS spatial analysis, social network analysis (SNA), and circuit theory is employed to develop both the ESP and the Recreational Spatial Pattern (RSP). A trade-off matrix is created to facilitate the reconstruction of the ESP, delineate functional zones, and identify strategic points, followed by a thorough optimization and development strategy. The analysis revealed 36 ecological source areas (ESAs) within Fuzhou City, encompassing a total area of 5807.90 km², predominantly situated in the western and northern regions. Additionally, 98 ecological corridors (ECs) were identified, extending over 2500.55 km, alongside 100 ecological pinch points (EPPs) and 146 ecological barrier points (EBPs). The city also contains 57 recreational nodes (RNs),, which display a spatial distribution characterized by a “dense in the east, sparse in the west” pattern. Furthermore, 165 recreational corridors (RCs) were extracted, covering a distance of 3795.21 km. Based on the trade-off matrix, Fuzhou City was categorized into eight functional zones: ecological core zone, ecological important zone, eco-recreation key trade-off zone, eco-recreation secondary trade-off zone, recreational core zone, recreational important zone, recreational development zone, and elastic development zone.The study identified 95 key strategic points and 475 sub-strategic. A multifunctional and complex ESP was constructed, characterized by “one core, five districts, six corridors, and seven wedges”, and a tailored ecological and recreational planning and development strategy for Fuzhou City was proposed. This research contributes a theoretical framework for the construction and optimization of a multifunctional ESP and supports the coordinated high-quality development of ecological protection and recreational activities in urban environments.